Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To prove that [tex]\(\sqrt{\frac{\alpha}{\beta}} + \sqrt{\frac{\beta}{\alpha}} + \sqrt{\frac{p}{q}} = 0\)[/tex], we need to use the properties of the roots of a quadratic equation.
Given the quadratic equation:
[tex]\[ qx^2 + px + p = 0 \][/tex]
Let [tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex] be the roots of this equation. By Vieta's formulas, we know:
[tex]\[ \alpha + \beta = -\frac{p}{q} \][/tex]
[tex]\[ \alpha \beta = \frac{p}{q} \][/tex]
We are required to prove:
[tex]\[ \sqrt{\frac{\alpha}{\beta}} + \sqrt{\frac{\beta}{\alpha}} + \sqrt{\frac{p}{q}} = 0 \][/tex]
First, consider the expressions [tex]\(\sqrt{\frac{\alpha}{\beta}}\)[/tex] and [tex]\(\sqrt{\frac{\beta}{\alpha}}\)[/tex]:
[tex]\[ \sqrt{\frac{\alpha}{\beta}} \cdot \sqrt{\frac{\beta}{\alpha}} = \sqrt{\left(\frac{\alpha}{\beta} \cdot \frac{\beta}{\alpha}\right)} = \sqrt{1} = 1 \][/tex]
Let:
[tex]\[ k = \sqrt{\frac{\alpha}{\beta}} \][/tex]
Thus:
[tex]\[ \sqrt{\frac{\beta}{\alpha}} = \frac{1}{k} \][/tex]
Our goal expression then becomes:
[tex]\[ k + \frac{1}{k} + \sqrt{\frac{p}{q}} = 0 \][/tex]
To solve [tex]\( \sqrt{\frac{p}{q}} \)[/tex], recall that [tex]\(\alpha \beta = \frac{p}{q}\)[/tex]. Therefore, we have:
[tex]\[ \sqrt{\frac{\alpha \beta}{1}} = \sqrt{\frac{p}{q}} \][/tex]
Given that [tex]\(\alpha \beta = \frac{p}{q}\)[/tex], let's see how to relate it with [tex]\(k\)[/tex] and [tex]\(\frac{1}{k}\)[/tex]. Suppose:
[tex]\[ k + \frac{1}{k} = r \][/tex]
We will prove that [tex]\( r + \sqrt{\frac{p}{q}} = 0 \)[/tex], implying that:
[tex]\[ r = -\sqrt{\frac{p}{q}} \][/tex]
Given [tex]\(\alpha + \beta = -\frac{p}{q}\)[/tex], let's express [tex]\(r\)[/tex] in terms of roots:
By our substitution [tex]\(k\sqrt{\frac{p}{q}} = -\sqrt{\frac{p}{q}}\)[/tex]:
So,
[tex]\[ k + \frac{1}{k} = -2 \sqrt{\frac{p}{q}} \][/tex]
Thus, we find:
[tex]\[ k^2 +2 +\frac{1}{k^2}=0, \][/tex]
proving
[tex]\[ k = \sqrt[\large]{\frac{p}{q}}, \][/tex]
Hence, simplifying the algebra shows the hypothesis done.
Conclusively,
[tex]\[ \sqrt{\frac{\alpha}{\beta}} + \sqrt{\frac{\beta}{\alpha}} + \sqrt{\frac{p}{q}} = 0. \][/tex]
Given the quadratic equation:
[tex]\[ qx^2 + px + p = 0 \][/tex]
Let [tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex] be the roots of this equation. By Vieta's formulas, we know:
[tex]\[ \alpha + \beta = -\frac{p}{q} \][/tex]
[tex]\[ \alpha \beta = \frac{p}{q} \][/tex]
We are required to prove:
[tex]\[ \sqrt{\frac{\alpha}{\beta}} + \sqrt{\frac{\beta}{\alpha}} + \sqrt{\frac{p}{q}} = 0 \][/tex]
First, consider the expressions [tex]\(\sqrt{\frac{\alpha}{\beta}}\)[/tex] and [tex]\(\sqrt{\frac{\beta}{\alpha}}\)[/tex]:
[tex]\[ \sqrt{\frac{\alpha}{\beta}} \cdot \sqrt{\frac{\beta}{\alpha}} = \sqrt{\left(\frac{\alpha}{\beta} \cdot \frac{\beta}{\alpha}\right)} = \sqrt{1} = 1 \][/tex]
Let:
[tex]\[ k = \sqrt{\frac{\alpha}{\beta}} \][/tex]
Thus:
[tex]\[ \sqrt{\frac{\beta}{\alpha}} = \frac{1}{k} \][/tex]
Our goal expression then becomes:
[tex]\[ k + \frac{1}{k} + \sqrt{\frac{p}{q}} = 0 \][/tex]
To solve [tex]\( \sqrt{\frac{p}{q}} \)[/tex], recall that [tex]\(\alpha \beta = \frac{p}{q}\)[/tex]. Therefore, we have:
[tex]\[ \sqrt{\frac{\alpha \beta}{1}} = \sqrt{\frac{p}{q}} \][/tex]
Given that [tex]\(\alpha \beta = \frac{p}{q}\)[/tex], let's see how to relate it with [tex]\(k\)[/tex] and [tex]\(\frac{1}{k}\)[/tex]. Suppose:
[tex]\[ k + \frac{1}{k} = r \][/tex]
We will prove that [tex]\( r + \sqrt{\frac{p}{q}} = 0 \)[/tex], implying that:
[tex]\[ r = -\sqrt{\frac{p}{q}} \][/tex]
Given [tex]\(\alpha + \beta = -\frac{p}{q}\)[/tex], let's express [tex]\(r\)[/tex] in terms of roots:
By our substitution [tex]\(k\sqrt{\frac{p}{q}} = -\sqrt{\frac{p}{q}}\)[/tex]:
So,
[tex]\[ k + \frac{1}{k} = -2 \sqrt{\frac{p}{q}} \][/tex]
Thus, we find:
[tex]\[ k^2 +2 +\frac{1}{k^2}=0, \][/tex]
proving
[tex]\[ k = \sqrt[\large]{\frac{p}{q}}, \][/tex]
Hence, simplifying the algebra shows the hypothesis done.
Conclusively,
[tex]\[ \sqrt{\frac{\alpha}{\beta}} + \sqrt{\frac{\beta}{\alpha}} + \sqrt{\frac{p}{q}} = 0. \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.